Medium Density Fibreboard Made of Acetylated Sludge from Paper Mill - Hakim, Luthfi; Herawati, Evalina; Wistara, I Nyoman Jaya (Makara Journal of Technology, 2011)
Medium Density Fibreboard Made of Acetylated Sludge from Paper Mill. Research of using sludge as raw material for making medium density fibreboard (MDF) was useful to create additional value of sludge. The objective of the research was to evaluate physical properties, mechanical properties, and durability of MDF from acetylated sludge in 4 levels of acetate anhydride (0%, 3%, 5%, and 7%) with 3 replicates. The MDF was made using dry process. After materials were mixed with adhesives, they were pressed using hotpress under 170 oC temperature and 45 Pa pressure for 25 minutes. The size of the MDF sample was 25 cm x 20 cm x 1 cm with 0.8 g/cm3 density. The physical properties (density, moisture content, water absorption, thickness swelling) and mechanical properties (modulus of elasticity, modulus of rupture, internal bond, screw holding power) was tested based on JIS A 5905-2003 standard. The durability was evaluated using SNI 01-7207-2006. All physical properties of MDF fulfill JIS A 5905-2003. Acetate anhydride decreased the moisture content value of MDF. On the other hand, all mechanical properties did not fulfill the standard. That was caused by calcium carbonate in sludge that blocked the adhesion between sludge fibres. The durability of MDF tested here was classified Class I which is very resistant to termites.